Analysis of New Marketing Initiatives on E-Commerce Platforms: A Case Study Based on Pinduoduo's "10 Billion Subsidies" - Li, Ruobing; Wang, Xueting; Wu, Shihong (Transactions on Economics, Business and Management Research, 2024)
In recent years, with the rapid development of Internet technology, the arrival of the e-commerce era has become an inevitable trend, more and more e-commerce platforms active in people's eyes, not only Taobao, 1688 and other veteran e-commerce platforms, but also with the Pinduoduo, Jitterbug and other emerging e-commerce forces are also gradually on the rise, which also makes the e-commerce industry, the market competition is intensifying, and in such a background, Pinduoduo in order to give consumers better quality service and want to stand out from the fierce market competition is difficult. In this context, Pinduoduo to provide consumers with better and better quality of service and want to stand out in the fierce market competition is difficult, so Pinduoduo to implement a new innovative marketing strategy - tens of billions of subsidy policy. Against this background, this paper analyzes the effect of Pinduoduo's 10 billion subsidies through literature research and online research and discusses its effect in depth in the light of Pinduoduo's actual situation.